Appeal for protection and the (incorrect) application of the proportionality test to the violation of 19 N°4 by security cameras: San Miguel Court of Appeals, judgment Rol P-3441-2016, March 20, 2017, Supreme Court, judgment Rol P-39-2017, December 19, 2016 - Rodríguez Rioseco, Nicolás; Gómez Sotomayor, Alejandro (Derecho Público Iberoamericano, 2021)
The article analyzes a judgment of the Court of Appeals of San Miguel in relation to the fundamental rights, in labor matters, of the workers and how the sentencer resolves the collision of rights between them and the employers, and whether it uses for its resolution the Proportionality Test or some modality of the same. In this specific case, there is a collision between the workers' right to privacy and the employers' right to freedom of enterprise and industrial property.